Reflections on Enhancing the Impact of Climate Risk Management Through Transformative Adaptation - Hellin, Jon; Fisher, Eleanor; Loboguerrero, Ana María (Frontiers in Climate, 2021)
Climate risk management is part of the response to the threat of climate change. Much effort has focused on the promotion on climate resilient agriculture. There has been undue focus on technology solutions per se and not enough attention on the coupling of technologies and socio-economics and how they become embedded in ecological systems underpinning smallholder agriculture. In this perspective, we argue that an intertwined social–ecological–technological systems approach to climate risk management is needed. Furthermore, in line with broader policy thinking on the need for transformative change towards sustainably living on the planet and ‘leaving no one behind’, a greater focus on transformative adaptation is required. Transformative adaptation tackles the root causes of vulnerability including unevenly distributed power relations, and extant networks of control and influence. There are, however, are relatively few examples of moving from the theory of transformative adaptation to practice. Three recent practical examples of transdisciplinary approaches, that we have direct experience of as researchers, provide lessons for initial ways forward as part of climate risk management initiatives. Examples from Vietnam, East and Southern Africa, and Guatemala illustrate the importance of inter- and transdisciplinary responses whereby the inequalities underlying unequal power structures may be addressed, enabling farmers to pursue climate risk management pathways that contribute to climate resilience and human development, as epitomized by the Sustainable Development Goals.